MEDIA FRAMING OF POLITICAL CONFLICTS - Vladisavljević, Nebojša (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2017)
By reporting on some conflicts but not on others, and by representing conflicts they report on in particular ways, the media strongly influence the dynamics and outcomes of democratisation conflicts, and thus also shape the prospects of success of conflict parties. This paper explores the literature on media and conflict by focusing on the ways in which media frame inter-state and civil wars, institutionalised conflicts and social movements in western democracies, and conflicts in nondemocratic and democratising states. Much of the literature discusses the ways in which western media frame foreign conflicts and domestic election campaigns and policy debates, while there is considerably less focus on domestic conflicts in nonwestern settings, such as those that arise during and after transitions from nondemocratic rule. There are only limited attempts to draw parallels between the media coverage of disparate conflicts. In contrast, this study builds upon research findings in these related areas to draw lessons for empirical research of media framing of the contentious dimension of contemporary democratisation. This study concludes that the political context is the main factor that shapes the media framing of various forms of political conflict. Several dimensions of the political context matter in this respect, such as regime type, international (foreign) or domestic perspective, elite consensus or conflict, policy consensus or uncertainty, policy area, more or less institutionalised nature of the political conflict at stake, and the stage of democratisation. Also, the literature suggests that media framing strongly influences political outcomes and thus fosters or undermines democratic institutions in new democracies.
Keywords: democratisation; democracy; nondemocratic regimes; social movements; protest; election campaigns; war; conflict; media frames